Modern CAD/CAM/CAE Systems: Brief Overview - Lyashenko, V.; Sotnik, S.; Manakov, V. (IJEAIS, 2021)
The article provides an overview of generalized CAD classification. Attention is focused on application of CAD / CAM / CAE in instrumentation. As result, 8 main criteria for choosing CAD / CAM / CAE instrumentation are proposed. The modern leaders in "medium-sized CAD" market are considered: SolidWorks, Autodesk Inventor, KOMPAS-3D and "heavy CAD" CATIA. Their functionality and features are described.
Keywords: design; modeling